Blood pressure control status of patients with hypertension on treatment in Dessie City Northeast Ethiopia - Zinabu Fentaw; Kidist Adamu; Shambel Wedajo (BMC, 2022)
Abstract Introduction Uncontrolled blood pressure contributes a huge contribution to many hypertension-related complications and it is one of the unbeaten problems for patients taking antihypertensive drugs. The association of social support and other factors with uncontrolled blood pressure during the covid-19 pandemic is not well investigated. Therefore, this study explored the determinants of blood pressure control status during the COVID-19 pandemic among patients with hypertension who were on an antihypertensive treatment. Method A cross-sectional study was done from March to May 2021 among adults aged 18 or more patients with hypertension for three months or more on treatment in Dessie City. An interview-administered questionnaire was done using simple random sampling from hypertension follow-up register for 380 patients with hypertension. Blood pressure measurement was taken from their arm using a stethoscope and mercury sphygmomanometer at a sitting position with 90-degree back support. Uncontrolled blood pressure was also computed either the systolic or diastolic blood pressure greater than or less than the limit of uncontrolled blood pressure with regarding the age and diabetic status of patients. The perceived social support-related questionnaire was adopted from the Multidimensional Scale of Perceived Social Support (MSPSS) -12 item checklist. It was sum-up and transformed into three categories using tertile of their computed raw scores. The adjusted prevalence ratio with a 95 percent confidence interval (CI) was used to calculate the strength of the association between uncontrolled blood pressure and independent predictors using log-binomial regression analysis. A P-value less than 0.05 was declared as statistically significant in multivariable log-binomial regression analysis. Result A total of 360 study participants were included in this study. The prevalence of uncontrolled blood measures in patients with hypertension with a 95% CI was 55.8(50.7, 61.0). In a multivariable analysis adjusted prevalence ratio with 95% CI for poor medication adherence 1.86(1.59,2.19), being male 1.35(1.11,1.64), secondary education 0.52(0.35,0.77), and low social support 1.24(1.01, 1.54) were the predictors of uncontrolled blood pressure. Conclusion Uncontrolled blood pressure for patients with hypertension on treatment is higher during the COVID-19 pandemic. Being male, poor medication adherence, educational status and low social support are factors that contribute to uncontrolled blood pressure.